Understanding deviance, crime, social control, and mass media: the construction of social order - Ziyanak, Sebahattin (Hamilton Books, 2022)
"Deviance through technology and media is explained. The authors then examine substance abuse, gun violence, terrorism, adolescent substance use, deviance and crime, fear of terrorism, gun violence, Kurdish pride gang, media exposure, secularization and modernity, social control, social order, and the impact of covid-19 on children's lives"--